The Prescription of Individualized Learning Strategies to an Adult Low-English Language Achiever: La prescripción individualizada de estrategias de aprendizaje a un adulto con bajo nivel de inglés (Papeles, 2022)
Teaching second language learning strategies suggests that it is necessary to teach students the operation and benefit of learning strategies. However, it is not yet clear why low-achieving students do not progress significantly even when relevant aspects of their learning are improved. This study focused on a 55-year-old adult language learner with low performance in learning English. A qualitative research methodology was followed through a semi-structured interview, needs analysis, and observation. The results indicated that teaching strategies aimed at improving a specific skill do not show a significant improvement in their performance when using English. However, the student showed the deployment of a series of strategies that helped him manage the speech situation. In addition, it was found that motivation takes on a significant relevance not only in the use of new strategies, but also in language learning.
Keywords: Learning strategies; Speaking skill; Strategy instruction